Pengaruh Kebijakan Insentif Pajak, Digitalisasi Pajak dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak UMKM - Riza Fitria; Dwi Fionasari; Dian Puji Puspita Sari (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2022)
The economy in Indonesia is dominated by micro, small and medium enterprises (MSME) based business activities. This business group is proven to be able to make a significant contribution. The number of MSMEs is increasing from year to year, providing an opportunity for the government to target this sector in an effort to increase taxes. This study aims to examine the effect of tax incentive policies, tax digitization and tax sanctions on MSME taxpayer compliance. In this study the method used for data collection is a questionnaire. The population in this study is individual MSME taxpayers in the city of Pekanbaru who are registered as taxpayers at KPP Pratama Pekanbaru Senapelan. Sampling using random sampling method, with a total sample of 100 respondents. This research is a quantitative study with data obtained using IBM Statistics SPSS 25. The results of the study show that the tax incentive policies, tax digitization and tax sanctions partially affect MSME taxpayer compliance.Keywords: Tax Incentive Policy, Tax Digitization, Tax Sanctions, Taxpayer Compliance